2004
DOI: 10.1590/s0101-81752004000400023
|View full text |Cite
|
Sign up to set email alerts
|

Preferência por hospedeiro e estratificação de Culicidae (Diptera) em área de remanescente florestal do Parque Regional do Iguaçu, Curitiba, Paraná, Brasil

Abstract: A investigação das populações de Culicidae em áreas de remanescentes florestais inseridas em área urbana, podem fornecer subsídios para compreensão dos processos de utilização de habitats apresentando diferentes graus de interferência antrópica. Foram investigadas espécies potencialmente zoofílicas durante o período vespertino no interior de remanescente florestal, no espaço urbano de Curitiba, Paraná. Durante o período de setembro de 2000 a junho de 2001, foram realizadas cinco coletas por estação, com auxíli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…squamipennis and Ma. flaveola were only captured on chickens, in agreement with the findings of other authors (Gabaldon et al 1977, Mitchell et al 1985, Forattini et al 1987, Teodoro et al 1994, Tissot & Navarro-Silva 2004). Ma.…”
Section: Discussionsupporting
confidence: 91%
“…squamipennis and Ma. flaveola were only captured on chickens, in agreement with the findings of other authors (Gabaldon et al 1977, Mitchell et al 1985, Forattini et al 1987, Teodoro et al 1994, Tissot & Navarro-Silva 2004). Ma.…”
Section: Discussionsupporting
confidence: 91%
“…Forattini et al (1989) observed distinct behavior by Ps. ferox , which reacted principally to human blood, and, in observations by Tissot and Navarro‐Silva (2004) and Molaei et al (2008), reacted to mammal blood. Although, the apparent prevalence of the mammals as hosts for this species in the studies of Molaei et al (2008) is likely a function of deer abundance and availability in the region of the northeastern United States.…”
Section: Discussionmentioning
confidence: 83%